The Effect of Soilaggregate Size and P Dosage On Amf Spores Number In Shorgum (Sorghum bicolor L.) - Samsu Samsu; Henry N Barus; Uswah Hasanah (Universitas Tadulako, 2017)
Mycorrhiza is a biological agent to help fertility of soil and plants. Application of mycorrhiza on the land in the form of inoculum is often used in agricultural land in the name of quality of inoculum that also influenced by the content of existing spores. One of them is growing medium. This study aimed to study the effect of soil aggregate size and P dosage on the number of mycorrhizal spores in sorghum plants. The research design used was Randomized Block Design consisting of 2 factors. First factor was soil aggregate size(μm) which consisted of 4 treatments: U1 = < 2000, U2 = 500 - 1000, U3 = 200 - 500, U4 = < 200, and second factor was P dosage: 100 mg/kg and 300mg/kg. Each treatment combination was repeated 3 times so that there were 24 units of experimental unit. Observation parameters included the percentage of the infected root, number of spores, plant height and dry weight of the plant. The research was conducted in Greenhouse and Agronomy Laboratory of Agricultural Faculty of Tadulako University Palu. The various sizes of soil aggregates do not affect the amount of arbuscular mycorrhizal spores in sorghum plants. P 100 mg/kg or f P 300 mg/kg dosage used do not address the effect of the mycorrhizal spores. There is no interaction between soil aggregate size and P dosage to the amount of mycorrhizal spores in sorghum plants.